Penaggulangan Kecanduan Game Online Mobile Legends Melalui Konseling Individual - Kosasih, Shinta Fitriani; Nurfathiyah, Aisyah; Perdana, Addin Haris; Saragi, Muhammad Putra Dinata (Konseling Edukasi : Journal of Guidance and Counseling, 2022)
Overcoming Addiction to Mobile Legends Online Games Through Individual Counseling. This study aims to Overcome Mobile Legends Online Game Addiction Through Individual Counseling. This research belongs to the type of library research, namely, by recording all findings and combining all findings, both theories and new findings from books, websites, articles and newspapers about overcoming online game addiction through individual counseling, analyzing all findings from various sources. reading and providing critical ideas about Overcoming Mobile Legends Online Game Addiction Through Individual Counseling. The results show that the individual counseling model will free up more time to help clients develop a more positive character. Individual counseling offers optimistic counseling techniques that assume everyone can progress, achieve goals, or receive positive evaluations so that they can overcome counselees with Mobile Legends Online Game Addiction. Keywords: Addiction Treatment, Online Gaming, Individual Counseling